2022
DOI: 10.47381/aijre.v32i3.340
|View full text |Cite
|
Sign up to set email alerts
|

Choosing A Rural Teaching Position: Recognizing the Importance of Relationships and Field Experiences

Abstract: This study reports the findings from a survey of 201 recent teacher education graduates from a university in the Northwestern United States regarding the factors that influenced their decision to take a teaching position in a rural or urban community following graduation. Results indicate that an in-depth rural practicum experience, being close to family, and the size of school influenced new graduates' decisions. Other factors such as school culture and administrative support were also found to be important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Many incentives are transactional, where teachers exchange their time in remote contexts for financial benefits. Versland et al's (2022) study in the USA also showed that teachers were attracted to rural locations because of financial benefits. Smaller class and school sizes, the welcome of the community and proximity to family are also attractants, and Versland et al (2022) acknowledge that these findings accord with Boylan's (1993) previous research amongst experienced RRR teachers in Australia that showed a gravitation toward forming strong relationships with students and community.…”
Section: Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Many incentives are transactional, where teachers exchange their time in remote contexts for financial benefits. Versland et al's (2022) study in the USA also showed that teachers were attracted to rural locations because of financial benefits. Smaller class and school sizes, the welcome of the community and proximity to family are also attractants, and Versland et al (2022) acknowledge that these findings accord with Boylan's (1993) previous research amongst experienced RRR teachers in Australia that showed a gravitation toward forming strong relationships with students and community.…”
Section: Literaturementioning
confidence: 99%
“…Versland et al's (2022) study in the USA also showed that teachers were attracted to rural locations because of financial benefits. Smaller class and school sizes, the welcome of the community and proximity to family are also attractants, and Versland et al (2022) acknowledge that these findings accord with Boylan's (1993) previous research amongst experienced RRR teachers in Australia that showed a gravitation toward forming strong relationships with students and community. That is, experienced teachers in RRR contexts had strong relationships with the people and geographies of those places.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations